Security problem in neoclassical realism - Setov, Nikita (De Securitate et Defensione. O Bezpieczeństwie i Obronności, 2016)
The article is dedicated to main approaches to security problem in neoclassical realism: B. Buzan’s concept of international politics, K. Holsti’s political theory, J. Mearsheimer’s “offensive realism” theory, S. Walt’s theory of “balance of threats”. Author pays special attention to state’s strategies on international arena.